DGI-059 Safety of Anti-Epidermal Growth Factor Receptor Agents: Cetuximab and Panitumumab. (12th March 2013) - Soriano, L; Redondo, S; Arcenillas, P; March, P; Garriga, R; Pla, R
Abstract : Background: A recently-published meta-analysis describes the risk of thromboembolic events (TEs) associated with anti-growth factor receptors such as cetuximab and panitumumab. Purpose: To describe the frequency of TEs related to cetuximab and panitumumab use. Likewise, to detail adverse reactions (ARs) and their severity. Materials and Methods: Retrospective descriptive study in a 500-bed university hospital performed from January 2010 to September 2012. All patients who had been treated with cetuximab or panitumumab were reviewed. In a database we recorded: sex, age, underlying disease, drug, dose reduction if it was necessary, number of cycles administered, ARs and degree of severity according to Common Toxicity Criteria. The information was extracted from patients' medical records and from pharmacy service records. Results: Twenty-four patients were included, 12 were men. Mean sample age was 61 years. The main underlying disease was colorectal cancer with liver and lung metastases (41.2%). Mean duration of treatment was 10.7 cycles/patient. All patients received cetuximab in combination regimens with fluoropyrimidines, platinum and irinotecan. Four patients were treated with panitumumab. ARs appeared in 95.8% of the sample. There were 153 ARs, 88.9% during treatment with cetuximab. (Table 1 ). Two cases of deep vein thrombosis (DVT) during treatment with cetuximab were reported; none with panitumumab. Grade 1 toxicity represented 44.5% of all ARs, 40.5% were grade 2, 13.7% grade 3 and 1.3% grade 4. Due to ARs, three patients required dosage reduction, all related to cetuximab schedules. Conclusions: Two cases of DVT were reported in patients treated with different cetuximab chemotherapy schedules. It is difficult to establish a relationship between ARs and the drugs used. Further studies are needed to clarify the association of TE and cetuximab. The rest of AR founded, are described in the product information. It is necessary a higher foresight to establish preventive measures to avoid or reduce AR toxicity. No conflict of interest.